2018
DOI: 10.1093/jac/dky109
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Escherichia coli STs and resistance mechanisms in sewage from Islamabad, Pakistan indicates a difference in E. coli carriage types between South Asia and Europe

Abstract: The most prevalent STs were ST394, ST10 and ST648, accounting for 39% of all isolates collected and were found at many sites across Islamabad. Carbapenemase genes were absent and only a single isolate of ST131 was found. The most prevalent resistance mechanisms were qnrS1 and blaCTX-M-15, with blaCTX-M-15 penetrating many STs and found in 31% of all collected isolates. However, the majority of the successful STs were blaCTX-M-15 negative indicating that resistance is not the main driver of prevalence. Twenty-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…A study conducted in the Netherlands found that ESBL-producing E. coli belonging to CC10 is present in a broad range of hosts, including humans, animals, and environmental surface water, with almost the same frequency (10%) (20). Moreover, CC10 has also been reported in the Danube River (Europe) (21), the Yamato River (Japan) (22), and sewage in Pakistan (23). A possible explanation is that CC10 circulates easily among different hosts and contains different types of carbapenemase genes.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in the Netherlands found that ESBL-producing E. coli belonging to CC10 is present in a broad range of hosts, including humans, animals, and environmental surface water, with almost the same frequency (10%) (20). Moreover, CC10 has also been reported in the Danube River (Europe) (21), the Yamato River (Japan) (22), and sewage in Pakistan (23). A possible explanation is that CC10 circulates easily among different hosts and contains different types of carbapenemase genes.…”
Section: Resultsmentioning
confidence: 99%
“…The only data on the distribution of the E. coli STs in South Asia come from three centers: Pune (19, 20), Kolkata (21), and Islamabad (22). Roy et al found that 6/67 isolates causing bacteremia on a neonatal intensive care unit were ST131 using a PCR-based method: no MLST was carried out (21).…”
Section: Resultsmentioning
confidence: 99%
“…Zahra et al surveyed the MLSTs of 110 E. coli isolates sampled from human sewage across multiple locations in Islamabad, Pakistan (22). Zahra and colleagues found 24 STs, with ST394, ST10, and ST648 predominating, with only 1/110 being ST131 (22).…”
Section: Resultsmentioning
confidence: 99%
“…In this approach, the relatedness between clusters of bacteria can be measured faster and more cost-effectively than by molecular methods, and more information regarding antimicrobial resistance can be obtained directly or indirectly, i.e., by detecting biomarkers associated with resistance to antimicrobial agents (144)(145)(146). We should also take into account that wholegenome sequencing is evolving very rapidly, especially with nanopore technology (147,148). The main advantage that MALDI-TOF MS offers is that information will be obtained at no additional cost besides those already incurred for identification purposes.…”
Section: Future Challengesmentioning
confidence: 99%